Understanding Indonesians' Intentions to Adopt Electric Vehicles: A Combination of Social Factors and Knowledge in the Theory of Planned Behavior and Technology Acceptance Model - Angga Adhiguna; Jennisa Junus HM; Rian Fajar Isnaeni; Sri Vista Limbong; Indria Handoko (Eduvest - Journal of Universal Studies, 2025)
Environmental damage caused by carbon emissions is driving various countries to seek sustainable solutions, one of which is through electric vehicle (EV) innovation. Electric vehicles are considered capable of reducing dependence on fossil fuels and lowering greenhouse gas emissions. However, in Indonesia, the adoption rate of electric vehicles by the public is still considered low. This study aims to empirically examine the influence of factors in the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) on Indonesians' intention to adopt electric vehicles. The approach used is quantitative with a survey method, involving 311 respondents who have knowledge or interest in electric vehicles. Data was collected through online questionnaires and analyzed using SPSS through multiple linear regression analysis. The results indicate that only moral norms, knowledge, and ease of use have a positive and significant influence on the intention to adopt electric vehicles. In contrast, subjective norms, perceived behavioral control, usefulness, and risk show no significant effect, while environmental concern has a negative influence, contrary to the proposed hypothesis. These findings highlight that personal factors